Kemampuan Berpikir Komputasional dalam Memecahkan Masalah Matematika - Ahmadsyah Fauzian Rambe; Yahfizam Yahfizam (International Forum of Researchers and Lecturers, 2024)
Computational thinking is the process of solving issues by using mathematical ideas and concepts. Systems problem solving, data analysis, abstraction, algorithms, and information representation are some of these ideas. The purpose of this study is to determine how mathematical problem-solving techniques for computational thinking function. Systematic literature observation was the research methodology employed in this study. A topic area of interest's existing research as well as pertinent, targeted research questions are found, reviewed, disseminated, and interpreted using the systematic literature review (SLR) technique. Journals may be found and evaluated methodically using the SLR approach, with each stage according to preset guidelines or rules.